The emergency plan for the use and management of the territory - La Rocca, Rosa Anna; Palermo, Annunziata; Viapiana, Maria Francesca (TeMA - Journal of Land Use, Mobility and Environment, 2021)
The issue of emergency planning in areas exposed to natural hazards cannot yet be considered as a focus within the scientific literature, probably because it has been judged as “too operative” for the interest of academic research. The topic of land use planning, spatial planning, and urban planning in risky areas, conversely, has gained attention in recent years. Nevertheless, the examples of good practices that involve ordinary master plans embedding mitigation concerns are still limited.